An investigation into multiple stage filters for high definition wavelength multiplexed networks - Rahman, Md. Mahmudur; Sharma, A.B.; Ahmed, Kazi Mohiuddin; Makelainen, Kimmo; Finnish International Development Agency (FINNIDA) (Bangkok : Asian Institute of Technology, 1994)
Fiber Fabry-Perot (FFP) filter is the most widely used optical demultiplexer in wavelength division multiplexing (WDM) networks for moderately dense channels because of its low insertion loss and wide free spectral range (FSR). FSR of the Fabry Perot filter depends inversely on the cavity length of the filter. Alignment and tuning fixture of the small cavity FFP makes its design complex and expensive. Also a large FSR FFP introduces adjacent channel crosstalk due to its large passband. The fiber Mach Zehnder (MZ) and ring filter is very simple in design. In this thesis an approach has been made not only to improve the performance of the FFP by cascading it with Mach-Zehnder or ring type filter but also to investigate the applicability of the other cascaded filter combinations in WDM networks. It has been found that a cascaded FFP- MZ and FFP Ring filter show better performances over the single stage FFP filter in terms of FSR and finesse.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Telecommunication; Optical fibers